Research on the Optimization of Urban Cold Chain Logistics System Based on the Example of Guangzhou. Issue 1 (January 2021) - Kuang, Mo; Du, Yong; Kuang, Da; Zhu, Xiangyi
Abstract: In view of the realistic environment of the cold chain logistics development in Guangzhou, this paper aims at analyzing the present pre-cooling equipment of the cold chain logistics in Guangzhou, the lack of cold storage facilities, the incomplete cold chain structure, the lagging of the development of the third-party cold chain logistics industry, the lack of trace ability of the products, the information tracking mechanism and the deficiency of the standard specifications of the cold chain, the shortage of cold chain professionals etc., and the countermeasures are put forward from three aspects: strengthening the policy support for the overall planning of the cold chain logistics; strengthening the construction and improvement of the cold chain logistics system and the platform and the main body; and developing the Guangzhou cold chain logistics industry in various modes.